Dari Gotong Royong ke Swipe dan Scroll: Transformasi Nilai Sosial dalam Kehidupan Masyarakat Indonesia - Annisa Putri; Eko Handoyo; Indriana Eko Armaidi (STKIP Subang, 2026)
The way people interact and communicate has changed significantly in recent years. Activities that were once carried out through direct face-to-face interactions are now increasingly conducted through social media and various digital platforms. This shift has influenced the social values that have long been embedded in Indonesian society, including gotong royong (mutual cooperation), which is recognized as one of the nation's cultural identities. This study aims to analyze the transformation of social values in Indonesian society from the culture of mutual cooperation to digital culture, as well as to examine the challenges and opportunities for preserving social values in the digital era. The study employed a library research method by utilizing relevant national and international journal articles as the primary sources of data. Data were collected through documentation techniques and analyzed using content analysis. The findings indicate that digital technology has transformed patterns of social interaction from physical spaces to digital environments. Nevertheless, the value of mutual cooperation has not disappeared; instead, it has adapted into more contemporary forms, such as online fundraising, digital social campaigns, and virtual communities. On the other hand, the digital era has also introduced challenges, including increasing tendencies toward individualism and reduced face-to-face social interaction. Therefore, efforts to preserve social values are needed through character education, digital literacy, and the responsible use of technology while maintaining the principles of togetherness and social solidarity.